Unveiling the Ideological Construction of Prabowo's First Presidential State Address a Critical Discourse Analytical Approach - Hanafi Wibowo; Elisa Nurul Laili; Umi Sholihah; Ali Mohammed Saleh Al-Hamzi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Prabowo Subianto's 2025 First State Address, a speech that has not been previously examined in academic literature. This study seeks to identify and analyse the linguistic and rhetorical strategies utilized in Prabowo’s speech to unmask his political legitimacy, presidential identity, ideological stance within the Indonesian context. Methodology: Using Teun A. van Dijk’s socio-cognitive model of Critical Discourse Analysis (CDA), the study analyzed both the transcript and video recording. Data were coded across macro, super, and micro levels to uncover thematic organization, argumentation patterns, and linguistic devices. Qualitative coding and multimodal cue analysis were employed by identifying recurring linguistic patterns (e.g., pronouns, metaphors, repetition) and correlating them with non-verbal features such as gestures, facial expressions and tone, to interpret how verbal and visual elements jointly construct ideological meaning. Findings: The analysis reveals that Prabowo frames his leadership as a moral and protective force against corrupt elites and economic exploitation. Nationalist appeals such as food self-sufficiency, poverty reduction, and empowerment of the wong cilik reinforce a paternalistic model of governance portraying the state as the guardian of the people. Toward the conclusion, he emphasizes democratic transition, international cooperation, and Indonesia’s global standing, invoking pride and collective dignity. Microstructural analysis of pronoun use, presuppositions, and metaphors demonstrates how rhetorical strategies align with broader ideological positioning. Conclusion: Prabowo’s first state speech address gives some theoretical contributions as the role of historical narratives in constructing collective cognition and sustaining political legitimacy. Originality: The originality of this research lies in its integrated application of van Dijk’s socio-cognitive framework to Prabowo Subianto’s 2025 State of the Nation Address which hasn’t been analyzed before, it combines textual and multimodal analysis to show how linguistic structures, visual cues, and rhetorical strategies work together to create political legitimacy and national identity.